2015
DOI: 10.1038/onc.2014.435
|View full text |Cite
|
Sign up to set email alerts
|

KLHL39 suppresses colon cancer metastasis by blocking KLHL20-mediated PML and DAPK ubiquitination

Abstract: Cullin 3 (Cul3)-family ubiquitin ligases use the BTB-domain-containing proteins for the recruitment of substrates, but the regulation of this family of ubiquitin ligases has not been completely understood. KLHL20 is a BTB-family protein and targets tumor suppressor promyelocytic leukemia protein (PML) and death-associated protein kinase (DAPK) to its kelch-repeat domain for ubiquitination and degradation. Here, we show that another BTB-kelch protein KLHL39 is recruited to the substrate-binding domain of KLHL20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…Here, we show that the silencing of LncKLHDC7B led to resistance to cell death. Similarly, it has been reported that silencing of members of the Kelch family leads to death resistance by anoikis and is associated with lower survival in colorectal cancer (Chen et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Here, we show that the silencing of LncKLHDC7B led to resistance to cell death. Similarly, it has been reported that silencing of members of the Kelch family leads to death resistance by anoikis and is associated with lower survival in colorectal cancer (Chen et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…We assessed the protein expression of WDR4 and PML in a cohort of 120 lung cancer patients. Immunohistochemical analydegradation has been observed in a number of cancer types (14,(18)(19)(20)(21)(22), and the ubiquitin ligases cullin 3-kelch-like family member 20 (CUL3-KLHL20) and ubiquitin protein ligase E3A (E6AP) are responsible for PML destruction in certain cancer types (18,22). However, the ubiquitin ligase that mediates PML degradation in lung cancer remains elusive, and the molecular mechanism for PML degradation in tumors has not been completely understood.…”
Section: Wdr4mentioning
confidence: 99%
“…With respect to CRC pattern 1, that is the only one showing up-regulation, we found reports of some novel genes included in this pattern that can be related to the progression of the disease, like for example squalene epoxidase (SQLE) that is up-regulated in breast cancer and indicates poor clinical outcome in early stages of this disease [29]. Another very interesting protein found in this CRC pattern is KLHL20, a BTB-kelch protein that is involved colon cancer metastasis since it is a substrate adaptor of CUL3 E3 ligase complex catalyzing the ubiquitination of DAPK (death-associated protein kinase) a well-known tumor suppressor [30]. …”
Section: Resultsmentioning
confidence: 99%